Targeting telomerase with radiolabeled inhibitors. - Waghorn, P; Jackson, M; Gouverneur, V; Vallis, K (Elsevier, 2016)
The expression of telomerase in approximately 85% of cancers and its absence in the majority of normal cells makes it an attractive target for cancer therapy. However the lag period between initiation of telomerase inhibition and growth arrest makes direct inhibition alone an insufficient method of treatment. However, telomerase inhibition has been shown to enhance cancer cell radiosensitivity. To investigate the strategy of simultaneously inhibiting telomerase while delivering targeted radionuclide therapy to cancer cells, (123)I-radiolabeled inhibitors of telomerase were synthesized and their effects on cancer cell survival studied. An (123)I-labeled analogue of the telomerase inhibitor MST-312 inhibited telomerase with an IC50 of 1.58 μM (MST-312 IC50: 0.23 μM). Clonogenic assays showed a dose dependant effect of (123)I-MST-312 on cell survival in a telomerase positive cell line, MDA-MB-435.